Protected cultivation to bring prosperity to horticultural growers - Dutt, Som (Indian Horticulture, 2019)
Keeping in view, the importance of the protected cultivation, Central Institute for Subtropical Horticulture, Lucknow, organized a two-day National Workshopcum- Seminar on â€œEmerging Prospects of Protected Cultivation in Horticultural Crops under Changing Climateâ€ during 22-23 December 2015 at Lucknow. Its main focus was to bring together a multi-disciplinary group of researchers, engineers, developmental agencies, manufacturers, policy-planners, farmers, NGOâ€™s and other stakeholders to discuss, deliberate and disseminate latest advancements on the issue and prepare a roadmap for improving horticultural production by extended use of these technologies. The event was concluded fruitfully with excellent recommendations.